The Elimination Et Choix Traduisant La Realite (ELECTRE) Method in Determining Priority for Acceptance of the Family Hope Program (Jorong Sawah Kareh Nagari Balimbing) - Sartika, Mira; Murni, Dewi (Universitas Negeri Padang, 2023)
Poverty is a hard issue to solve. Therefore the government held a program to help reduce poverty, namely the Family Hope Program (FHP). However, the problems that occur are that there are still FHP recipients who are not on target. Where the ELECTRE method is the method used to determine ranking by considering the importance level criterion of each, in cases with other alternatives but only a criterion is involved. The results of the study using the ELECTRE method obtained that the alternative that was prioritized for FHP beneficiaries was the alternative with the top ranking, for the number of alternatives that were prioritized depending on the decision maker, namely the Nagari Balimbing office.